Sensorless control of motoring/generating system for future more-electric turboprop aircraft - Fan, Linhui (2021)
Multiphase electrical machines have gained increased attentions recently due to its fault tolerance capability which is of great importance for more-electric aircraft (MEA) application. The object of this research is a dual three-phase permanent magnet synchronous machine (PMSM) motoring/generating system for future more-electric turboprop aircraft. Sensorless control is required because the designed system is fit in a harsh environment with severe volume restrictions for installing mechanical speed/position sensors required for standard control approaches. Another challenge is due to the asymmetric winding structure of the employed machine; hence the well-established machine mathematical models could not be directly transformed from stationary coordinates to dq rotating frame complication the field oriented control (FOC) of the machine. To address this issue, an XYZ modelling approach is proposed which not only simplifies the mathematic model but also makes the FOC achievable. Different sensorless strategies are reviewed and compared among which Model Reference Adaptive System (MRAS) is selected as it is robust and simple in implement. The major drawback of this method is the sensitivity to machine parameter variation. To solve this problem, an enhanced MRAS is proposed to identify machine parameter drift. Based on observability analysis, it proves that no more than one parameter could be identified simultaneously for a MRAS based rotor speed sensorless system. After comparison between rotor resistance, rotor inductance and permanent magnet (PM) flux, the last parameter is selected to be the identification subject, and a PM flux estimation based MRAS sensorless system is designed for mid- and high-speed operation. Since MRAS fails at low speed range, an I/F start-up strategy is applied, and a hybrid sensorless control method is proposed for full-speed range operation. A switching operation is designed for smooth transition between these two methods. Experimental results show good performance of the proposed hybrid approach and verified the key theoretical findings of this research.